Social Defence Measures and Insanity: Problems and Solutions - Filatova, Maria; Alekseeva, Tatiana (GLOSSAE. European Journal of Legal History, 2023)
The influence of sociological law theory on the criminal law of the RSFSR1 and the USSR resulted in introduction of the concept of social defence. Several legal acts and draft criminal codes reflected the idea of “dangerousness of a person” as a general category. Soon after, however, scholars began to draw more attention to particular categories of dangerous offenders, and different psychiatric issues were discussed. It was clear that social defence measures against sane and insane offenders could not be the same, but many questions were left unresolved. Lawmakers soon removed the most extreme concepts of sociological law thought, which were adopted in the early 1920s. Nevertheless, a connection between insane and juvenile offenders and the idea of social defence has persisted and some unresolved questions remain almost exactly the same. Insanity and related issues remain some of the most difficult theoretical obstacles in contemporary Russian criminal law.